An equivalent structural stress-based fatigue evaluation framework for rib-to-deck welded joints in orthotropic steel deck. (1st October 2019) - Li, Jun; Zhang, Qinghua; Bao, Yi; Zhu, Jinzhu; Chen, Lu; Bu, Yizhi
Highlights: A fatigue evaluation framework based on the equivalent structural stress is presented to predict fatigue failure mode of the rib-to-deck welded joints. An analytical model of root-weld crack is established to determine the critical cracking plane. Effect of the weld penetration ratio on the fatigue failure mode transition is investigated. Master S - N curve is employed to predict the fatigue life for rib-to-deck welded joint. Abstract: Rib-to-deck welded joints in orthotropic steel decks have demonstrated different fatigue failure modes that have different fatigue resistance. Among the different failure modes, the mode corresponding to the lowest fatigue resistance governs the fatigue resistance of the welded joint. The ability of determining the governing failure mode is essential for predicting the fatigue resistance of the welded joints. This research establishes a fatigue evaluation framework for determining the dominant failure mode of rib-to-deck welded joints. The framework is established based on the equivalent structural stress method and validated using model test data. The results indicate that the proposed framework provides accurate prediction of the dominant fatigue failure mode of rib-to-deck welded joints. Based on the presented framework, the fatigue resistance of the welded joints is reasonably predicted, and the effect of weld penetration ratio on the fatigue failure mode is investigated.